The JA‐pathway MYC transcription factors regulate photomorphogenic responses by targeting HY5 gene expression. (4th January 2020) - Ortigosa, Andrés; Fonseca, Sandra; Franco‐Zorrilla, José M.; Fernández‐Calvo, Patricia; Zander, Mark; Lewsey, Mathew G.; García‐Casado, Gloria; Fernández‐Barbero, Gemma; Ecker, Joseph R.; Solano, Roberto
Summary: Jasmonates are key regulators of the balance between defence and growth in plants. However, the molecular mechanisms by which activation of defence reduces growth are not yet fully understood. Here, we analyze the role of MYC transcription factors (TFs) and jasmonic acid (JA) in photomorphogenic growth. We found that multiple myc mutants share light‐associated phenotypes with mutants of the phytochrome B photoreceptor, such as delayed seed germination in the dark and long hypocotyl growth. Overexpression of MYC2 in a phyB background partially suppressed its long hypocotyl phenotype. Transcriptomic analysis of multiple myc mutants confirmed that MYCs are required for full expression of red (R) light‐regulated genes, including the master regulator HY5 . ChIP‐seq analyses revealed that MYC2 and MYC3 bind directly to the promoter of HY5 and that HY5 gene expression and protein levels are compromised in multiple myc mutants. Altogether, our results pinpoint MYCs as photomorphogenic TFs that control phytochrome responses by activating HY5 expression. This has important implications in understanding the trade‐off between growth and defence as the same TFs that activate defence responses are photomorphogenic growth regulators. Significance Statement: Activation of defences reduces growth, which affects crop yield. The molecular mechanisms underlying this trade‐off are not fully understood. We found that MYC transcription factors that regulate jasmonate‐dependent plant defences are also photomorphogenic growth regulators required for expression of red light‐regulated genes. Our results show that defence and growth are tightly coordinated by the action of MYCs and suggest strategies to uncouple this trade‐off to increase plant responses to stress without a growth penalty.